2020
DOI: 10.1186/s13613-020-00656-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with major adverse kidney events in patients who underwent veno-arterial extracorporeal membrane oxygenation

Abstract: Objective: To describe acute kidney injury (AKI) natural history and to identify predictors of major adverse kidney events (MAKE) within 1 year in patients supported by veno-arterial extracorporeal membrane oxygenation (VA-ECMO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…Similar results have been reported for lactate as a surrogate for tissue hypoperfusion, which remains high in some patients despite VA-ECMO [ 21 ]. The frequent development of end-organ failure including acute kidney injury in patients on VA-ECMO [ 22 , 23 ], further suggests insufficient end-organ perfusion in some patients. We show that, compared to patients with cerebral damage, patients with persistent shock were older, more frequently underwent in-hospital cardiac arrest, and had shorter low-flow durations.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported for lactate as a surrogate for tissue hypoperfusion, which remains high in some patients despite VA-ECMO [ 21 ]. The frequent development of end-organ failure including acute kidney injury in patients on VA-ECMO [ 22 , 23 ], further suggests insufficient end-organ perfusion in some patients. We show that, compared to patients with cerebral damage, patients with persistent shock were older, more frequently underwent in-hospital cardiac arrest, and had shorter low-flow durations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, AKI patients with RRT initiation after ECMO could well represent a different population phenotype, which intravascular hemolysis secondary to the extracorporeal circuit plays a more central role in the pathophysiology of AKI. Findings from the French study of an association between MAKE at 1 year and the number of RBC packs received while on ECMO align with this theory (15). The other possibility is that early initiation of RRT in patients with severe cardiac or respiratory failure who require ECMO is associated with favorable long-term renal outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…Despite these major differences in study design, the Taiwanese study results seem consistent with our findings. In a single-center study from France, Vinclair et al (15) examined factors associated with MAKE in a cohort of patients requiring venoarterial ECMO (VA-ECMO). Interestingly, this study found that baseline eGFR, KDIGO AKI stage at ECMO cannulation, and the number of RBC packs received while on ECMO were associated with MAKE at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…All three patients with AKI underwent mechanical ventilation and ECMO, and it was difficult to distinguish whether AKI was caused by SARS-CoV-2 infection or was associated with treatments, such as ECMO and vancomycin. 24 25 Therefore, it is possible that the incidence of AKI related to COVID-19 was overestimated. In fact, all three patients used both ECMO and vancomycin, and AKI developed after vancomycin use.…”
Section: Discussionmentioning
confidence: 99%